2013
DOI: 10.2147/ott.s41069
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of prognostic significance of CD109 expression in women with vulvar squamous cell carcinoma

Abstract: ObjectiveThe goal of this study was to investigate the between cluster of differentiation 109 (CD109) expression and tumor diameter, invasion depth, tumor grade, presence of lymph-node metastasis, and overall survival in patients with vulvar squamous cell carcinoma, which is the most common type of vulvar cancer.MethodTwenty-six patients who underwent an operation for vulvar cancer between 1999 and 2009 in our clinic were included in this study. Immunohistochemical staining was performed on formalin-fixed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Similarly, Dong and co-workers showed that CD109 is expressed in bladder squamous cell carcinomas and adenosquamous carcinomas but not in adenocarcinomas or normal gallbladder tissue [ 33 ]. A positive correlation has been reported between CD109 expression and tumour grade in patients with vulvar squamous cell carcinoma [ 37 ]. More recently, CD109 was found highly expressed in penile squamous cell carcinoma and to be a key regulator of the progression of lower-grade glioma and therefore a potential molecular target for therapy [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dong and co-workers showed that CD109 is expressed in bladder squamous cell carcinomas and adenosquamous carcinomas but not in adenocarcinomas or normal gallbladder tissue [ 33 ]. A positive correlation has been reported between CD109 expression and tumour grade in patients with vulvar squamous cell carcinoma [ 37 ]. More recently, CD109 was found highly expressed in penile squamous cell carcinoma and to be a key regulator of the progression of lower-grade glioma and therefore a potential molecular target for therapy [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CD109 has also been detected in NPC stem-like cells. Moreover, recent studies have revealed that CD109 is overexpressed in multiple human cancers, including squamous cell carcinoma of the lung [ 92 ], vulva [ 93 ] and uterine cervix [ 94 ], adenosquamous carcinoma of the gallbladder [ 95 ], and ductal adenocarcinoma of the pancreas [ 96 ]. Recently, a meta-analysis has proved the association between the high level of CD109 expression and poor overall survival in cancer patients, suggesting the use of CD109 as a prognostic [ 97 ].…”
Section: The Application Of Aptamer-based Biomarker Discovery In Vari...mentioning
confidence: 99%